Genetic potential of maize full-sib progenies subjected to a reciprocal recurrent selection - Pedro, César; Marçola, Maria Angélica; Charimba, Alcides Mário; Queiroz, Lorena Gabriela Coelho de; Souza, João Cândido de (Pesquisa Agropecuaria Brasileira, 2024)
The objective of this work was to quantify the genetic potential of full-sib maize progenies subjected to a reciprocal recurrent selection, in order to obtain high-yielding hybrids. The experiment was carried out in the alpha lattice design, with three replicates and 24 blocks. One hundred and two full‑sib maize progenies, from the crossing of two populations and two checks, were evaluated for the following traits: grain yield, seed mass, number of ears per plant, days to maturity, days to anthesis, days to silking, anthesis-silking interval, ear height, plant height, ear position, and stem lodging. Genetic parameters were estimated through REML/BLUP and multivariate analyses (correlation and similarity network, cluster heat map, and genetic gains). There are genetic variability and divergent clusters among the studied full-sib maize progenies. Seed mass, number of ears per plant, and anthesis‑silking interval are the traits that most contribute to the improvement of grain yield and divergence among the full-sib maize progenies. Genetic potential should be exploited through the selection and recombination in reciprocal recurrent selection to obtain high-yielding hybrids.